Pedicle Screw Fixation with Kyphoplasty Decreases the Fracture Risk of the Treated and Adjacent Non-treated Vertebral Bodies:a Finite Element Analysis - 杨攀 章莹 丁焕文 刘坚 叶林强 肖进 涂强 杨涛 王非 孙国刚 (华中科技大学学报：医学英德文版, 2016)
Adjacent vertebral fractures are common in patients with osteoporotic vertebral compression fractures(OVCFs) after kyphoplasty.This finite element study was to examine whether short segment pedicle screw fixation(PSF) with kyphoplasty may decrease the fracture risk of the treated and adjacent non-treated vertebrae after kyphoplasty for OVCFs.By simulating cement augmentation with or without short segment pedicle screw fixation(PSF),two tridimensional,anatomically detailed finite element models of the T10–L2 functional spinal junction were developed.The insertion of pedicle screws into the intact vertebra apparently decreased the stress distribution of the treated vertebra in vertical compression and other load situations.The stress distribution in the bone structures of the intact vertebra adjacent to the intact-screwed vertebra was much less than that in the one adjacent to the treated vertebra.The insertion of pedicle screws into the intact vertebra greatly decreased the maximum displacement of the cortical bones and cancellous bones of the vertebrae.Our results indicated that short segment PSF with kyphoplasty may decrease the fracture risk of the treated and adjacent non-treated vertebrae in the management of OVCFs.